Do ICT Development and labor force foster Economic Growth in Indonesia? - Siti Mudrikah; Muhammad Fathrul Quddus (International Journal of Management, Business, and Social Sciences, 2023)
Purpose: This paper aims to determine the ICT Development Index and other supporting variables affecting Indonesia's economic growth.Methods: This study uses secondary data from 1996-2019. Using economic growth variables as endogenous variables, and labor force, gross fixed capital formation (GFCF), cellular phones per 100 people, fixed telephones per 100 people, and internet users as exogenous variables. The data analysis technique used OLS multiple linear regression with eviews 9 application.Finding: The neoclassical theory developed by Solow (1957) a name "Growth Accounting" that economic growth formed from the factors of production and technology. This finding only the variable Mobile cellular per 100 people does not affect economic growth in Indonesia, and other variables are significant.Novelty: This study uses an innovation variable, namely the ICT Development Index, to complement the variables of production factors (labor and GFCF). This study focuses on Indonesia because it is about Indonesia's potential use of technology and information, among indications of the use of telephone and internet users in Indonesia.Implications: Further research can apply other ICT Development variables such as ICT exports or use the other countries.Keyword: GDP, Gross Fix Capital Formation, Internet User, Labor Force.